DESAIN STRATEGI BERBASIS KONTEKSTUAL PADA PEMBELAJARAN STATISTIKA DAN METODOLOGI PENELITIAN - Usman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The problem to be analyzed in this study is how to design a contextual method in learning "Statistics and Research Methodology?". While the purpose of this study is to create a contextual approach design in teaching Statistics and Research Methodology. This research applies the research and development (R&D) method. In this research, only the initial stage is presented, namely the creation of a learning model by designing a Statistics and Research Methodology learning program that utilizes a contextual approach. There are seven principles in the steps of the contextual approach to teaching Statistics and Research Methodology, namely 1) Constructivism; 2) Discovery; 3) Questions; 4) Learning Community; 5) Modeling; 6) Reflection; and 7) Authentic Assessment. After the trial, to evaluate the effectiveness of the developed approach, it is necessary to implement it in the classroom.